Detecção e genotipagem de papilomavírus humano em mulheres infectadas com vírus da imunodeficiência humana - MORAIS, Ana Cléa Cutrim Diniz de (2022)
Introduction and objective: Human papillomavirus (HPV) and human immunodeficiency virus (HIV) are the two most prevalent sexually transmitted infections (STI) worldwide. The HIV virus is one of the risk factors for infection with HPV. This study aimed to detect HPV, identify its specific types in cervical, anal and oral mucosa of HIV-positive women, and investigate the viral load, CD4 and CD8. Methods: This is a cross-sectional study with a quantitative approach. The sample was composed of 86 HIV-positive women on antiretroviral therapy. The participants answered a survey about sociodemographic data, contraceptive use, sexual and reproductive history. CD4 and CD8 T cell counts and viral load obtained from the electronic medical records of the specialized service. Biological samples (cervical, anal and oral) were collected using sterile swabs in the routine gynecological outpatient service at the research units. Nucleic acid extraction performed using the QIAamp DNA Mini Kit™ (QiagenR). Detection of HPV-DNA performed by nested polymerase chain reaction (PCR) amplification using PGMY09/11 primers. Genotyping submitted to the Sanger sequencing technique. Data were categorized according to presence or absence of DNA-HPV, presence of DNA-HPV in one or more anatomical sites, and DNA-HPV low and high oncogenic risk. For analyses, a significant p value < 0.05 considered. The tests performed in the statistical program IBM SPSS version 24. Results: HPV DNA detected in 54.7%; being 65.9%, cervico-vaginal, 63.8% in anal canal and 4.2% in oral mucosa; 29.8% cervico-vaginal and anal canal concomitantly and 2.12% in cervico-vaginal, anal and oral canal simultaneously. Viral load ≥75 HIV copies/ml was associated with the presence of HPV. Among the genotyped samples there was a higher prevalence of DNA-HPV type 6, low risk (34.0%), followed by the types of high oncogenic risk 59 (17.0%) and 16 (14.9%). The cervical site showed higher prevalence of high-risk HPV. There was an association between viral load and HPV of low oncogenic risk. Conclusion: There was a high frequency of HPV infection in HIV-seropositive women, especially in the cervical and anal sites. HPV 6 (low oncogenic risk) was the most frequent, followed by HPV types 59 and 16 (high risk).